2012
DOI: 10.1093/icesjms/fss152
|View full text |Cite
|
Sign up to set email alerts
|

Cod catches taken by the German recreational fishery in the western Baltic Sea, 2005–2010: implications for stock assessment and management

Abstract: Strehlow, H. V., Schultz, N., Zimmermann, C., and Hammer, C. 2012. Cod catches taken by the German recreational fishery in the western Baltic Sea, 2005–2010: implications for stock assessment and management. – ICES Journal of Marine Science, 69: 1769–1780. Next to the commercial fishery, the recreational fishery plays an important role in the removal of biomass from fish stocks. In this study, we present estimates of German recreational cod (Gadus morhua) catches in the western Baltic Sea between 2005 and 2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 19 publications
3
49
0
2
Order By: Relevance
“…Thus, although the presented release proportions were based on the most current catch estimates, the calculated release proportions may only be representative for these particular years. The two German surveys showed that the release proportions for Baltic cod caught in German (Strehlow et al, 2012). This is in line with the finding that German anglers mainly release fish that are not legal to retain.…”
Section: Release Proportions and Motivationssupporting
confidence: 79%
See 3 more Smart Citations
“…Thus, although the presented release proportions were based on the most current catch estimates, the calculated release proportions may only be representative for these particular years. The two German surveys showed that the release proportions for Baltic cod caught in German (Strehlow et al, 2012). This is in line with the finding that German anglers mainly release fish that are not legal to retain.…”
Section: Release Proportions and Motivationssupporting
confidence: 79%
“…In recent years, following the introduction of European legislation requiring estimation of recreational catches of some species, recreational fisheries have gained increasing attention in European fishery research and management. For example, a recent study in Germany showed that the recreational harvest of cod (Gadus morhua) in the western Baltic Sea accounted for 34 -70% of the German commercial cod landings, indicating that total fishing mortalities need to be adjusted, and that the stock was more productive than previously assumed (Strehlow et al, 2012). As a result of this study, the recreational Baltic Sea cod harvest has been included in the stock assessment since 2013.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, there are frequent conflicts between recreational and professional fishermen (Mendonça, 2014;Teramoto and Diegues, 2014), which is valid also for the rivers studied in this paper (Matulić et al, 2010;Smederevac-Lalic et al, 2012). It became increasingly relevant for fish management to understand the impact of recreational fishing on commercially fished stocks and vice versa (Strehlow et al, 2012;Griffiths and Fay, 2015;Marengo et al, 2015). Therefore, in this research we compare the official data on both kinds of fishing on the Sava and Danube rivers in Croatia and Hungary, before the commercial fishery in Hungary was banned in 2016 (Hirado.…”
Section: Introductionsupporting
confidence: 54%